The good people [compact disc, unabridged] - Kent, Hannah, 1985- (Hachette Book Group, 2017)
Hedged in by gossip and joined by their desperation, three women in nineteenth-century Ireland are drawn together in the hope of rescuing a child from a superstitious community.